A Meta-analytic Systematic Review and Theory of the Effects of Perceived Listening on Work Outcomes - Avraham N. Kluger; Michal Lehmann; Herman Aguinis; Guy Itzchakov; Galit Gordoni; Jetmir Zyberaj; Cafer Bakaç (Journal of Business and Psychology, 2023)
The quality of listening in interpersonal contexts was hypothesized to improve a~variety of work outcomes. However, research of this general hypothesis is dispersed across multiple disciplines and mostly atheoretical. We propose that perceived listening improves job performance through its effects on affect, cognition, and relationship quality. To test our theory, we conducted a registered systematic review and multiple meta-analyses, using three-level meta-analysis models, based on 664 effect sizes and 400,020 observations. Our results suggest a strong positive correlation between perceived listening and work outcomes, r= .39, 95% CI 0.167em=0.167em[.36, .43], ρ= .44, with the effect on relationship quality, r=.51, being stronger than the effect on performance, r=.36. These findings partially support our theory, indicating that perceived listening may enhance job performance by improving relationship quality. However, 75% of the literature relied on self-reports raising concerns about discriminant validity. Despite this limitation, removing data solely based on self-reports still produced substantial estimates of the association between listening and work outcomes (e.g., listening and job performance, r= .21, 95% CI 0.167em=0.167em[.13, .29], ρ= .23). Our meta-analyses suggest~further research into~(a) the relationship between listening and job knowledge, (b)~measures assessing poor listening behaviors, (c)~the incremental validity of listening in~predicting listeners' and speakers' job performance, and~(d) listening as~a means to improve relationships at work.
Keywords: 650; Listening; Relationships; Affect; Cognition; Job performance